2019
DOI: 10.5692/clinicalneurol.cn-001270
|View full text |Cite
|
Sign up to set email alerts
|

A case of anti-titin antibody positive nivolumab-related necrotizing myopathy with myasthenia gravis

Abstract: 59:431 はじめに ニボルマブは,本邦で開発された免疫チェックポイント阻 害薬(immune checkpoint inhibitors; ICIs)で,従来の抗がん 剤や分子標的薬とは異なる新しいがん治療薬である 1) .2014 年に悪性黒色腫に対する適応で発売され,その後多くの悪性 腫瘍に適応が拡大したが,それと共に様々な臓器に対する免 疫関連有害事象(immune-related adverse event; irAE)が発生 している 2) 3) .神経系では筋炎や重症筋無力症(myasthenia gravis; MG)が知られており,ときに重症化するため注意が 必要である 4) ~ 6) .我々は,ニボルマブ投与後に高 CK 血症を 伴う MG 症状で発症し,四肢体幹の筋力低下はなかったが, 抗横紋筋抗体が陽性で,筋生検で炎症性の壊死性ミオパチー の所見を認めた症例を経験したので報告する. 59:434 マクロファージ,CD4,CD8 陽性リンパ球浸潤を主体とした 炎症所見を認める点が特徴的である 14) .本例では,さらに CD20 陽性リンパ球も動員され,MHC class I 陽性筋線維の分… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thus, irAE-MG results in facial and bulbar paralysis, such as dysarthria, more frequently than idiopathic MG. Recently, three cases of anti-striational antibody-positive nivolumab-related MG complicated by myositis have been reported ( Table ) ( 21 - 23 ). These three patients presented with ophthalmoplegia and bulbar paralysis, similar to the patient in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, irAE-MG results in facial and bulbar paralysis, such as dysarthria, more frequently than idiopathic MG. Recently, three cases of anti-striational antibody-positive nivolumab-related MG complicated by myositis have been reported ( Table ) ( 21 - 23 ). These three patients presented with ophthalmoplegia and bulbar paralysis, similar to the patient in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these antibodies have been associated with MG subtypes and disease severity (32,33), and patients with idiopathic MG who were positive for anti-Kv1.4 antibody generally showed a higher frequency of myasthenic crisis that was more severe than that in patients who were positive for anti-titin antibody (34)(35)(36). Recent case reports of irAE-MG have shown that patients with anti-Kv1.4 antibodies and anti-titin antibodies, as well as those with only anti-titin antibodies, also had a severe clinical course (21)(22)(23). Although the clinical course of patients with irAE-MG and idiopathic MG could not be determined to be similar, our patient had only anti-Kv1.4 antibodies that resulted in MGFA class V, a severe manifestation of MG. Further case studies are needed to determine the cause of the difference between cases of irAE-MG with both anti-titin and anti-Kv1.4 antibodies and those with either antibody after administration of nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing myositis is a known side effect of immune checkpoint inhibitors (ICIs), with a rate of 1% reported with anti-programmed cell death protein-1 (PD-1) antibody use. 24 , 25 , 26 In a recent review of orbital myositis, McNab identified 17 reported ICI-associated cases. 27 Most patients were using ipilimumab, a checkpoint inhibitor that targets cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), though none of these cases were biopsied and therefore it is unknown whether muscular necrosis occurred.…”
Section: Discussionmentioning
confidence: 99%